PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN KETERAMPILAN BERBICARA DAN PRESTASI BELAJAR SISWA - Elida Ariani; Nina Kurniah (DIADIK, 2022)
This research is conducted  to describe the application of talking stick type of cooperative learning model to increase the speaking skill and the students’ achievement at English Lesson of the tenthgrade at SMA Negeri 1 Kikim Timur. The research methods that used were Classroom Action Research and Quasi Experiment. The subjects of this research were students of the tenth grade SMA Negeri 1 Kikim Timur at the second semester of the academic year 2020/2021,for CAR class was X IPS 1,Experiment class X IPS 3,and Control Class X IPS 2. Each class totaling 27 students. The Research instruments used observation sheet and test. The data analysis used the average score analysis and test consisting of inter-cycle different test and unrelated two sample different test. The result showed  that the application of cooperative type of learning model talking stick can increase the speaking skill and the students’ achievement of the tenthgradestudents of English lesson at SMA Negeri 1 Kikim Timur